THE EFFECT OF OWNERSHIP STRUCTURE AND CASH FLOW TO THE NON-FINANCIAL FIRMS’ DIVIDEND PAYOUT RATIO LISTED IN IDX - Regina Aria Putri; Rofikoh Rokhim (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. The aim of this study is to analyze the effect of ownership structure and cashflow to the non-financial firms’ dividend payout ratio listed in Indonesian StockExchange (IDX). The samples of this study are 63 firms over the period 2009 – 2013.This study conducted in panel regression analysis using the random effect modelapproach. The result of regression found that largest shareholder and governmentownership give a positive effect to the payment of dividend. While institutionalownership and operating cash flow give a negative impact to the payment of dividend.Keywords: dividend, ownership structure, cash flowAbstrak. Penelitian ini bertujuan untuk menganalisis pengaruh ownership structuredan cash flow terhadap dividend payout ratio pada perusahaan non-keuangan yangterdaftar di Indonesia Stoack Exchange (IDX). Sampel penelitian ini adalah 63perusahaan dengan periode penelitian tahun 2009 – 2013. Penelitian ini dilakukandengan menggunakan panel regression analysis dengan pendekatan random effectmodel. Hasil regresi menunjukkan bahwa largest shareholder dan governmentownership memberikan pengaruh positif yang signifikan terhadap pembayaran dividen.Sementara institutional ownership dan operatingcash flow memberikan pengaruh negatif yang signifikan terhadap pembayaran dividen.Kata kunci: dividen, struktur kepemilikan, arus kas